2021
DOI: 10.1111/1759-7714.13900
|View full text |Cite
|
Sign up to set email alerts
|

Glasgow prognostic score for prediction of chemotherapy‐triggered acute exacerbation interstitial lung disease in patients with small cell lung cancer

Abstract: Background: Predicting the incidence of chemotherapy-triggered acute exacerbation of interstitial lung disease (AE-ILD) in patients with lung cancer is important because AE-ILD confers a poor prognosis. The Glasgow prognostic score (GPS), which is an inflammation-based index composed of serum levels of C-reactive protein and albumin, predicts prognosis in patients with small cell lung cancer (SCLC) without ILD. In this study, we investigated AE-ILD and survival outcome based on the GPS in patients with ILD ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“… 2 , 12 , 13 Therefore, predicting ILD exacerbation may be beneficial in improving the prognosis of lung cancer with ILD. Although studies have already identified usual interstitial pneumonia patterns in high‐resolution computed tomography (HRCT), low forced vital capacity, Gender‐Age‐Physiology score, and Glasgow prognostic score (GPS) as predictors of exacerbation, 9 , 10 , 12 , 14 , 15 clinically effective factors that can reliably predict exacerbations have yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 , 12 , 13 Therefore, predicting ILD exacerbation may be beneficial in improving the prognosis of lung cancer with ILD. Although studies have already identified usual interstitial pneumonia patterns in high‐resolution computed tomography (HRCT), low forced vital capacity, Gender‐Age‐Physiology score, and Glasgow prognostic score (GPS) as predictors of exacerbation, 9 , 10 , 12 , 14 , 15 clinically effective factors that can reliably predict exacerbations have yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Although the etiology of sarcopenia remains unclear, chronic inflammation and malnutrition due to regulation of myokine production have been considered causative factors. 16 Our group have previously reported that GPS, which is calculated using serum C‐reactive protein and albumin, can predict the prognosis and exacerbation of ILD in patients with ILD‐complicated lung cancer, 14 , 15 suggesting the potential involvement of inflammation and nutrition in the pathophysiology of this disease. Therefore, the present study sought to determine whether the psoas major muscle area at the third lumbar vertebral level on CT, which has been used as an index that reflects the entire skeletal muscle mass, 28 could potentially be a biomarker for predicting exacerbation of ILD and overall survival (OS) in patients with ILD‐complicated lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…After acute myocardial infarction (AMI), the inflammatory response is vital in myocardial remodelling [ 23 , 24 ]. The Glasgow Prognostic Score (GPS) assesses serum albumin and C-reactive protein levels [ 25 ]. A drop in serum albumin level indicates a severe inflammatory response in the patient [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…After AMI, the in ammatory response plays an important role in myocardial remodeling [19,20]. The Glasgow prognosis outcome scoring system assesses serum albumin and C-reactive protein levels [21]. When the serum albumin level drops, the patient has a severe in ammatory response [22].Therefore, the Glasgow prognosis score can accurately re ect the degree of the in ammatory response.…”
Section: In Ammatory and Noafmentioning
confidence: 99%